Słowiański kompleks Europy? Wzajemne relacje między Bułgarami a Zachodem - Moroz-Grzelak, Lilla (Slavica Lodziensia, 2019)
The aim of the article was to show the relationship between Bulgaria and Europe in the past and of the present-day. The material used here comprises the texts of Western authors who perpetuated and still perpetuate the condescending treatment of Bulgarians and Bulgaria. The opinions of the Bulgarians about Europe were also presented. It was observed that the negative image of this country is determined by its location in the Balkans. The literature of the Western authors has preserved the idea of the Balkans as a battlefield between East and West, between barbarity and civilization. The border between Europe and the Balkans was understood in the past as a journey from civilization into the wild, from freedom to tyranny. Undoubtedly, the centuries of Turkish rule have left its mark on the inhabitants and culture of the Balkans. Bulgarians inhabiting a part of the Balkan Peninsula automatically found themselves in a part of the continent ill-perceived by the “Western world”. On the other hand, among the Bulgarians, as part of the Slavic world, there is a complex of underestimation and pursuit of Europe. Terms and wording related to the backwardness and catching up with Europe have become an element of the Bulgarian discourse. Bulgarian thinking duplicates stereotypes about the glory of the West and the Europeanization which they aspire to.